Proses Psikologis Pembelajaran Bahasa Indonesia di Perguruan Tinggi (Pendekatan Kognitif dan Afektif) - Muhamad Maimun; Kholid Kholid (Indo-MathEdu Intellectuals Journal, 2023)
Indonesian learning at the college level demands a deep understanding and proper use in a variety of communication contexts. This study aims to explore the psychological processes involved in Indonesian learning in higher education using cognitive and affective approaches. This study uses a qualitative approach with a case study research method. The study participants consisted of final year students who took Indonesian courses at the Institut Agama Islam (IAI) Qamarul Huda Bagu Peringgarata Lombok Tengah. Data was collected through classroom observation, interviews, and document analysis. The data is then analyzed using thematic analysis to identify patterns of psychological processes that emerge during learning Indonesian. The results showed that the psychological processes involved in Indonesian learning in higher education involve cognitive and affective aspects simultaneously. The cognitive aspect involves understanding grammar, vocabulary, and problem-solving abilities in the context of Indonesian communication. The affective aspect involves intrinsic and extrinsic motivation, attitudes toward Indonesian learning, and levels of confidence in using Indonesian.These findings have important implications in curriculum development and Indonesian learning methods in higher education